The Electromagnetic Spectrum of Neutron Stars - Baykal, Altan; Yerli, Sinan K.; Inam, Sitki C.; Grebenev, Sergei; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
Neutron stars hold a central place in astrophysics, not only because they are made up of the most extreme states of the condensed matter, but also because they are, along with white dwarfs and black holes, one of the stable configurations that stars reach at the end of stellar evolution. Neutron stars posses the highest rotation rates and strongest magnetic fields among all stars. They radiate prolifically, in high energy electromagnetic radiation and in the radio band. This book is devoted to the selected lectures presented in the 6th NATO-ASI series entitled "The Electromagnetic Spectrum of Neutron Stars" in Marmaris, Turkey, on 7-18 June 2004. This ASI is devoted to the spectral properties of neutron stars. Spectral observations of neutron stars help us to understand the magnetospheric emission processes of isolated radio pulsars and the emission processes of accreting neutron stars. This volume includes spectral information from the neutron stars in broadest sense, namely neutrino and gravitational radiation along with the electromagnetic spectrum. We believe that this volume can serve as graduate level of text including the broad range of properties of neutron stars.
Neutron Star Formation -- Young Neutron Stars and Their Wind Nebulae -- Neutron Star Superfluidity, Dynamics and Precession -- A Biography of the Magnetic Field of a Neutron Star -- Elementary Processes in Strong Magnetic Fields -- Drifting Subpulses in PSR B0826-34 -- Temperature Distribution in Magnetized Neutron Star Crusts -- Coupling of Radial and Non-Radial Oscillations of Neutron Stars -- High-Energy Neutrino Astronomy -- Gravitational Wave Interactions with Magnetized Plasmas -- The Double-Neutron-Star Inspiral Rate and Expectations for Gravitational-Wave Detection -- Proto-Neutron Star Neutrino Emission -- Observations of Cooling Neutron Stars -- Optical Studies of Isolated Neutron Stars and Their Environments -- Disks Around Radio Pulsars -- Radiation from Condensed Surface of Magnetic Neutron Stars -- Observations of Radio Pulsars -- Radio Pulsar Statistics -- Emission Mechanisms and Broad Band Spectra of Pulsars -- Modeling Spectral Features from Isolated Neutron Stars -- Formation and Evolution of Neutron Stars in Binary Systems -- Accretion Disks -- High Mass X-ray Binaries in LMC -- Astrophysics with Lobster Telescopes -- The Stability of Magnetized Rotating Plasmas with Strong Toroidal Fields -- Accretion Powered X-Ray Pulsars -- Delayed Iron Lines In GX 1+4 -- Timing Neutron Stars -- Millisecond X-Ray Pulsars and QPOs -- The Electromagnetic Spectrumof AXPS -- The Distribution of Khz QPO Frequencies in Sco X-1 -- The Chandra X-Ray Observatory -- The Integral Mission -- Concluding Remarks.
Keywords: PHYSICS; ASTRONOMY; ASTROPHYSICS; RELATIVITY (PHYSICS).; PHYSICS; ASTRONOMY; ASTROPHYSICS; EXTRATERRESTRIAL PHYSICS, SPACE SCIENCES; ASTRONOMY, ASTROPHYSICS AND COSMOLOGY; RELATIVITY AND COSMOLOGY